2016
DOI: 10.1515/jpem-2015-0254
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and self-esteem levels in obese children: a case-control study

Abstract: Our results indicate that obese children may experience psychiatric disorders more than normal-weight peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 7 publications
1
30
0
2
Order By: Relevance
“…Increased risk of small intestinal bacterial overgrowth (28) and different gut microbiota composition (29) in obesity has been reported which might contribute to gastrointestinal dysmotility, excessive fermentation, altered visceral perception and gut permeability with their metabolites leading to pain-predominant FGID (30,31). Finally, obesity and FGID share common psychological comorbidities, such as stress, depression, and anxiety, which can contribute to each other's development and aggravate each other (32,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of small intestinal bacterial overgrowth (28) and different gut microbiota composition (29) in obesity has been reported which might contribute to gastrointestinal dysmotility, excessive fermentation, altered visceral perception and gut permeability with their metabolites leading to pain-predominant FGID (30,31). Finally, obesity and FGID share common psychological comorbidities, such as stress, depression, and anxiety, which can contribute to each other's development and aggravate each other (32,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Al comparar el estado nutricional y la autoestima no se detectaron diferencias estadísticas (p> 0,05), distinto a lo encontrado en adolescentes obesos, los cuales alcanzaron menores niveles de ésta variable y con tasas significativamente más altas de depresión y ansiedad (21). Niños coreanos obesos, obtuvieron menores niveles de autoestima que los sujetos con peso normal, y la obesidad infantil puede estar relacionada con insatisfacción corporal, lo que lleva a una baja autoestima y altos niveles de síntomas depresivos (22).…”
Section: Discusionunclassified
“…Alternately, Topcu et al [8] found obese children may experience psychiatric disorders to a greater degree than normal weight children. According to this group, the heightened anxiety and depression of the obese children-could be due to their need to seek more comfort laden foods, but could also suggest a negative feedback cycle of obesity, heightened depression, and anxiety, fewer social interactions, and more challenges with energy balance along with emotion driven eating.…”
Section: Overviewmentioning
confidence: 99%